Deep Learning through a STEM-Integrated Project-Based Learning Model for Enhancing Students’ Creativity - Ilyas; Mulia Rahmi; Muchsin; Safrijal (Jurnal Penelitian Pendidikan IPA, 2026)
21st-century education demands that students not only master basic knowledge but also develop critical, creative, and problem-solving skills. These skills can be enhanced through Project-Based Learning (PjBL) integrated with STEM within a deep learning framework. This qualitative case study involved 11th-grade students at SMAN 1 Simpang Tiga, using observations, interviews, and project document analysis, with data analyzed via the Miles and Huberman’s interactive model. The findings reveal that STEM-integrated PjBL creates an open, contextual learning environment that encourages active idea exploration, diverse perspectives, and interdisciplinary projects combining science, technology, engineering, and mathematics, leading to deep problem-solving. The model also fosters greater student enthusiasm and emotional engagement throughout the learning process. This study suggests that integrating PjBL-STEM in deep learning effectively builds a collaborative, reflective, and creative learning culture. Additionally, it highlights the crucial role of teachers as facilitators who design authentic, meaningful learning experiences that stimulate student creativity.